Adaptive Leadership and Policy Relevance in Encouraging Citizen Responses Regarding Local Cultural Education and Preservation Programs in West Java: Kepemimpinan Adaptif dan Relevansi Kebijakan dalam Mendorong Respon Warga Mengenai Program Pendidikan dan Pelestarian Budaya Lokal di Jawa Barat - Sefti Nurannisa Ruswika; Rachmawati, Ike; Siti Nur Syipa; Ateng Sutisna (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
This study aims to analyze the influence of adaptive leadership style and program relevance on citizen responses to education and cultural preservation programs in West Java. The study employed a quantitative approach with a causal explanatory design, using a survey method with 400 respondents selected using proportional random sampling from Bandung City, Cirebon Regency, and Garut Regency. The research instrument was a questionnaire based on a 1–5 Likert scale. Data analysis was performed using multiple linear regression, including classical assumption tests, t-tests, F-tests, and coefficients of determination. The results showed that adaptive leadership style and program relevance simultaneously and partially had a positive and significant effect on citizen responses. Partially, program relevance was found to be more dominant (β=0.581; Sig. 0.000) than adaptive leadership style (β=0.272; Sig. 0.012). The Adjusted R² value of 0.435 indicates that the model is able to explain 43.5% of the variation in citizen responses, while the remaining 56.5% is influenced by factors outside the model. These findings confirm that the combination of adaptive leadership and programs relevant to community needs is an important foundation for increasing public participation.